Microbial Technologies Employed for Biodegradation of Neonicotinoids in the Agroecosystem - Ahmad, Sajjad; Cui, Dongming; Zhong, Guohua; Liu, Jie (Frontiers in Microbiology, 2021)
Neonicotinoids are synthetic pesticides widely used for the control of various pests in agriculture throughout the world. They mainly attack the nicotinic acetylcholine receptors, generate nervous stimulation, receptor clot, paralysis and finally cause death. They are low volatile, highly soluble and have a long half-life in soil and water. Due to their extensive use, the environmental residues have immensely increased in the last two decades and caused many hazardous effects on non-target organisms, including humans. Hence, for the protection of the environment and diversity of living organism’s the degradation of neonicotinoids has received widespread attention. Compared to the other methods, biological methods are considered cost-effective, eco-friendly and most efficient. In particular, the use of microbial species makes the degradation of xenobiotics more accessible fast and active due to their smaller size. Since this degradation also converts xenobiotics into less toxic substances, the various metabolic pathways for the microbial degradation of neonicotinoids have been systematically discussed. Additionally, different enzymes, genes, plasmids and proteins are also investigated here. At last, this review highlights the implementation of innovative tools, databases, multi-omics strategies and immobilization techniques of microbial cells to detect and degrade neonicotinoids in the environment.